Macrophages in tumor cell migration and metastasis - Friedman-DeLuca, Madeline; Karagiannis, George S.; Condeelis, John S.; Oktay, Maja H.; Entenberg, David (Frontiers in Immunology, 2024)
Tumor-associated macrophages (TAMs) are a phenotypically diverse, highly plastic population of cells in the tumor microenvironment (TME) that have long been known to promote cancer progression. In this review, we summarize TAM ontogeny and polarization, and then explore how TAMs enhance tumor cell migration through the TME, thus facilitating metastasis. We also discuss how chemotherapy and host factors including diet, obesity, and race, impact TAM phenotype and cancer progression. In brief, TAMs induce epithelialmesenchymal transition (EMT) in tumor cells, giving them a migratory phenotype. They promote extracellular matrix (ECM) remodeling, allowing tumor cells to migrate more easily. TAMs also provide chemotactic signals that promote tumor cell directional migration towards blood vessels, and then participate in the signaling cascade at the blood vessel that allows tumor cells to intravasate and disseminate throughout the body. Furthermore, while chemotherapy can repolarize TAMs to induce an anti-tumor response, these cytotoxic drugs can also lead to macrophage-mediated tumor relapse and metastasis. Patient response to chemotherapy may be dependent on patient-specific factors such as diet, obesity, and race, as these factors have been shown to alter macrophage phenotype and affect cancer-related outcomes. More research on how chemotherapy and patient-specific factors impact TAMs and cancer progression is needed to refine treatment strategies for cancer patients.